Applicability of Ambulatory Cleft Lip Repair in North-western Nigeria: Case Series and Review of the Existing Literature - Abdulrazaq Olanrewaju Taiwo; Ramat Oyebunmi Braimah; Adebayo Aremu Ibikunle; Olufemi Ibrahim Adigun; Sikiru H Lawal; Bruno Ile-Ogendengbe; Mujtaba Bala; Adeyemi Micheal Olayinka; Moshood Folorunsho Adeyemi; Mohammed A Farouk (Wolters Kluwer Medknow Publications, 2022)
Objective: To report the applicability of ambulatory cleft lip repair (CLR) and to review the existing literature. Materials and Methods: This is a retrospective clinical case series study of ambulatory CLR in North-western Nigeria. The study was carried out in Usmanu Danfodiyo University Teaching Hospital (UDUTH), Sokoto, between January 2012 and December 2018. Relevant clinical data of the subjects obtained include sociodemographics, type of cleft, and complications. Protocol employed includes premedication with diazepam (0.5 mg/kg, IV) slowly, followed by administration of glycopyrrolate (0.005 mg/kg, IV) and diclofenac potassium (1 mg/kg, IV). Then, ketamine (0.1 mg/kg, IV) was infused slowly over a 5-min period to achieve procedural sedation (Ramsey sedation score of 3). The data were analyzed using (SPSS; Chicago, IL, USA) program, version 20. The results were presented in simple descriptive statistics. Results: The age ranged from 2 to 21 years with male preponderance (M: F = 4:1). All participants had unilateral clefts lip with or without alveolus. The left side was twice involved as the right. There were no perioperative complications nor mortality recorded and no patient required conversion to general anesthesia. All patients were successfully discharged home on the same day of the operation. No case of readmission was recorded and subsequent follow-up was uneventful. Conclusions: Parenteral use of ketamine and diazepam for outpatient pediatric cleft lip procedures is safe and of immense benefits in reducing the surgical cleft burden without compromising patients safety.